Closure to “closed-form heave solutions for expansive soils” - Rao, R. Rama (2011)
During the past decade, the theory for heave prediction has developed within the context of unsaturated soil behavior and has become a valuable tool for geotechnical practice. The laboratory procedures for testing expansive soils have also been essentially standardized. The heave prediction theory is briefly reviewed in this paper, and the importance of sampling disturbance is emphasized. Closed‐form solutions are presented for several possible situations that can be applied to engineering practice. In all cases, the soil deposit is assumed to be homogeneous, and the swelling pressure is assumed to be constant with depth.